2021
DOI: 10.1111/sifp.12150
|View full text |Cite
|
Sign up to set email alerts
|

Not All Women Who Experience Side Effects Discontinue Their Contraceptive Method: Insights from a Longitudinal Study in India

Abstract: Side effects are a primary reason why women stop using contraception, even though they may still want to avoid a pregnancy. The Demographic and Health Surveys (DHS), the largest source of nationally representative data on contraceptive discontinuation, only asks women who discontinued a method their reasons for discontinuation, for which side effects is an option. Yet, side effects are also experienced by continued users. Using longitudinal data collected from a cohort of contraceptive users in Odisha and Hary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Despite the high burden of side effects, many women continued using their initial contraceptive method. Our findings are consistent with recent evidence from a cohort study in India, which found that half of women who experienced side effects were still using their initial method at 6 months 44 . Adjusting for side effects, risk of discontinuation was higher among women who felt ‘very dissatisfied’ with their method but not among those who were less than fully satisfied with their method.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Despite the high burden of side effects, many women continued using their initial contraceptive method. Our findings are consistent with recent evidence from a cohort study in India, which found that half of women who experienced side effects were still using their initial method at 6 months 44 . Adjusting for side effects, risk of discontinuation was higher among women who felt ‘very dissatisfied’ with their method but not among those who were less than fully satisfied with their method.…”
Section: Discussionsupporting
confidence: 90%
“…We also did not measure the individual’s ability to access affordable contraceptive services should they wish to switch or discontinue their current method (which, in the case of LARC methods, requires provider removal). All of these may be important explanatory factors in switch and discontinuation 44,48 . Even where contraceptive services are available and generally free, recent evidence from Kenya has shown that provider barriers to LARC removal may restrict women’s ability freely to decide to switch or stop LARC use 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This limits our ability to compare our findings to other studies and underscores the critical need to explore these areas of contraceptive use and experience more fully. We also note that we did not assess severity or frequency of side-effects; women who experience more severe side-effects or more frequent side-effects may discontinue at higher rates than others as Jain and colleagues found in India, adding further nuance to understanding the effect of side-effects on contraceptive behavior [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tolerability of specific side-effects may differ for a variety of social, cultural, and economic reasons; how side-effects are interpreted, treated (e.g. availability and accessibility to menstrual hygiene products or treatment for cramping), and the economic and physical consequences when they are experienced are heavily influenced by context and quality of available services [ 6 , 10 , 24 26 ]. Findings from high-income countries should not, therefore, be applied to LMIC contexts nor should findings from one LMIC be rotely applied to another.…”
Section: Introductionmentioning
confidence: 99%